2007
DOI: 10.2984/1534-6188(2007)61[437:baiopi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Impacts of Pacific Island Invasive Species. 3. The African Big-Headed Ant, Pheidole megacephala (Hymenoptera: Formicidae)

Abstract: In the Pacific region,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 53 publications
4
94
0
2
Order By: Relevance
“…Pheidole megacephala and L. humile began their worldwide dispersal in the 19th century and have already spread through much of their potential range (Wetterer et al 2009;Wetterer 2012). However, several other highly destructive ants have thus far come to occupy only a small portion of their potential ranges, most notably the red imported fire ant (Solenopsis invicta) (Wetterer 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Pheidole megacephala and L. humile began their worldwide dispersal in the 19th century and have already spread through much of their potential range (Wetterer et al 2009;Wetterer 2012). However, several other highly destructive ants have thus far come to occupy only a small portion of their potential ranges, most notably the red imported fire ant (Solenopsis invicta) (Wetterer 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The study of the impacts of invasive ants on oceanic islands has received a lot of attention, especially regarding the impacts on the vulnerable native fauna (e.g. Davis et al, 2010;Wetterer 2007;O'Dowd et al, 2003). In the last years, however, more studies have found that the effects of invasive ants on continental ecosystems may be just as dramatic as those on islands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier papers, I have reviewed the worldwide spread of many of these cosmopolitan ant species, including some that have become major global pests, incurring great ecological and economic damage, e.g., Anoplolepis gracilipes (Smith), Linepithema humile (Mayr), Pheidole megacephala (Fabricius), Solenopsis geminata (Fabricius), Solenopsis invicta Buren, and Wasmannia auropunctata (Roger) (Wetterer 2005, 2012, 2013a, b, Wetterer et al 2009). …”
Section: Introductionmentioning
confidence: 99%